Pathophysiology and management of renovascular hypertension - Łukasz Dobrek (Polish Pharmaceutical Society, 2020)
Renovascular hypertension is one of the essential cases of secondary arterial hypertension, accounting for about 1-5% of all hypertensive cases. Despite a relatively low prevalence, 10-45% cases with this type of hypertension develop severe hypertension, which is resistant to standard antihypertensive therapy, even involving the administration of three hypotensive agents. Renovascular hypertension development is a consequence of hemodynamically significant narrowing (stenosis) of the renal artery or its major branches, most often determined by the presence of atherosclerotic changes or the fibromuscular dysplasia located in the renal vessels. The impairment of the renal blood flow initiates a cascade of pathophysiological disturbances, related to the activation of the renin-angiotensin-aldosterone system and the endothelin system and leads to the development of renal endothelial dysfunctions and increased oxidative stress in kidney tissues. As a consequence, in the course of advanced renal artery stenosis and renovascular hypertension, there is a risk of ischemic nephropathy development, with pathological, pro-inflammatory and pro-fibrotic remodeling of the kidney tissues, resulting in chronic kidney disease and failure. However, in the detailed pathophysiological description of renovascular hypertension, three basic scenarios can be distinguished, taking into account: (1) the presence of both kidneys, with one affected by stenosis, (2) the presence of both stenotic kidneys, or (3) stenosis of a solitary kidney. Depending on the aforementioned assumptions, renovascular hypertension may be a high-resistance one or it may develop as an entity mainly determined by an expansion of intravascular volume. The article is a narrative review, briefly summarizing issues related to pathophysiology, diagnostics and treatment of renovascular hypertension. The aim of the paper was to systematize the knowledge of pharmacists who also provide pharmaceutical care to patients with this type of hypertension.